Purifying the Soul, Healing the Age: The Relevance of Al-Ghazali’s Concept of Happiness in Responding to Contemporary Spiritual Crisis - Bintar Asror Syaffutra; Sudarman; Zarkasi, Ahmad (IAIN Parepare, 2025)
This study aims to explore Al-Ghazali’s concept of happiness as elaborated in his work Kīmiyā’ al-Sa‘ādah and to critically analyze its relevance in addressing the spiritual and ethical crisis of contemporary society. The research departs from the concern that the modern understanding of happiness is largely materialistic, short-term, and psychologically fragmented, often resulting in existential anxiety and spiritual emptiness. Al-Ghazali offers a holistic framework of happiness rooted in self-knowledge (ma‘rifat al-nafs), soul purification (tazkiyat al-nafs), and spiritual ascension toward divine knowledge (ma‘rifatullāh), combining both individual and social dimensions of well-being. This research employed a qualitative descriptive-analytical method with a library research approach, using Kīmiyā’ al-Sa‘ādah as the primary source and supported by relevant academic literature and field data. The study finds that happiness in Al-Ghazali’s perspective is a transformative process that involves ethical cultivation, self-discipline, and spiritual awareness. Furthermore, it responds meaningfully to modern spiritual disconnection and the weakening of social ethics. The findings also reveal that Al-Ghazali’s conception of happiness aligns with, yet transcends, modern psychological models by integrating the vertical (God-human) and horizontal (human-human) dimensions of life. It offers not only an inner sense of peace but also serves as a foundation for moral and social harmony. Based on these findings, the study recommends the integration of Al-Ghazali’s values into spiritual education, character formation programs, and contemporary counseling practices. It also proposes further interdisciplinary research between Islamic philosophical traditions and contemporary psychological sciences to enrich the discourse on meaningful and holistic happiness in the 21st century.